Labour Relations and Asset Returns - Danthine, Jean-Pierre; Donaldson, John B. (Review of Economic Studies, 2002)
This paper proposes a dynamic GE model with standard business cycle properties that also achieves a satisfactory replication of the major financial stylized facts. We ride on two major ideas. First, we show that operating leverage, originating in the priority status of wage claims given the observed business cycle characteristics of the latter, magnifies the risk properties of the residual payments to firm owners and justifies a substantial risk premium. Further we build on the observation that the low frequency variations in income shares constitute a significant source of risk, one that is unlikely to be insurable. When we price this risk in an incomplete market framework, we obtain a GE model with return volatilities close to observations and a sizable equity premium. This is accomplished in a world of low risk aversion and standard utility function but with agent heterogeneity. Workers with restricted access to financial markets are insured by firms and the consumption and preferences of firm owners solely determine the pricing kernel.